CO-BUILDING: THE EXCHANGE NETWORK OF BRICKS AND RELATED BUILDING TECHNOLOGY AROUND DUTCH FORMOSA (1624-1662) - I Chun Huang (PEOPLE: International Journal of Social Sciences, 2025)
The formation of buildings is not only based on design theories but also relies heavily on the extensive construction networks behind them, which is especially true and often more complex under the colonial system of the Dutch East India Company (VOC) in Asia. This study focuses on the sources and transportation of brick materials, as well as the dissemination of brickmaking and bricklaying techniques, during the construction of key fortifications in Dutch Formosa. By analyzing brick quantity records in VOC’s Taiwan-related documents, such as the De Dagregisters van het Kasteel Zeelandia (Diary of Castle Zeelandia), the research reconstructs the timeline of brick imports from the southeast China coastal area to Tayouan (now Anping, Tainan). It also infers the local brick production capacity in Saccam (now downtown Tainan) based on the scale of Fort and City Zeelandia. In addition, historical records reveal that bricks were exported from Tayouan to other settlements in Taiwan, as well as to Hirado, Japan. As VOC power and territorial control expanded in Taiwan, brickmaking techniques spread to places like Wankan and Tamsui, primarily under the control of Chinese immigrants who managed brick burning and masonry work. Meanwhile, fortifications construction during this period featured the use of Dutch cross-bond masonry, a technique still visible in the remains of Castle Zeelandia. This study situates these developments within the framework of “co-colonization,” highlighting the interconnected exchange networks that went beyond mere commodity trade and uncovering a fusion of building traditions between colonizers and the colonized.